Islam and its Teachings: A Vital Means to the Problem and Perception of Gambling among Muslims of Nasarawa North Senatorial District Nigeria - Ibrahim Shekarau Dahiru; Shuaibu Mahmud Nasidi (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: Gambling is a pervasive issue that negatively impacts individuals and communities globally, including among Muslims, despite its explicit prohibition in Islam. This study aims to explore the prevalence, causes, and consequences of gambling among Muslims in the Nasarawa North Senatorial District, with a focus on understanding the role of Islamic teachings in addressing this problem. Theoretical Framework: The theoretical framework of this study is grounded in Islamic principles, particularly the prohibition of gambling as stated in the Qur'an and Hadith, which highlight its moral and social consequences. A review of relevant literature reveals that gambling is not only an economic concern but also a moral and psychological issue, often resulting in addiction and community deterioration. Literature Review: Furthermore, the literature emphasizes the critical role of religious education in mitigating such behaviours. Methods: The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to provide a comprehensive analysis of the issue. Data collection involved gathering responses from Muslim participants in the study area, focusing on their perceptions and experiences with gambling. Results: The findings reveal that gambling is prevalent among the respondents, with addiction emerging as a significant problem. Many gamblers lack sufficient knowledge of Islamic teachings on gambling, which contributes to their continued engagement in this prohibited activity. Interviews further highlight the societal and economic challenges faced by gamblers, including financial instability and family disintegration. The study concludes that Islam and its teachings play a vital role in addressing gambling, but the persistence of this issue is largely attributed to a lack of awareness and understanding of these teachings. Implications: As an implication, the research underscores the need for enhanced Islamic education and awareness programs. Community-based initiatives, such as counselling and support groups, are recommended to prevent and address gambling among Muslims in the region. Novelty: The novelty of this study lies in its focus on the intersection of gambling and Islamic teachings within a specific Muslim community, providing valuable insights into how religious principles can be leveraged to tackle modern social issues. By emphasizing the role of Islamic education and community engagement, this research contributes to a broader understanding of effective strategies for mitigating gambling and its harmful effects on the Ummah.